Melrose and Croc find a smile - Chichester Clark, Emma. (London : HarperCollins Children's Books, 2006)
Croc helps his friend Melrose find his smile by taking him for a fun-filled day in the country.
2.1
K-3
Keywords: Crocodiles -- Juvenile fiction; Dogs -- Juvenile fiction; Landscape -- Juvenile fiction; Crocodiles -- Fiction; Dogs -- Fiction; Landscape -- Fiction; Crocodiles -- Fiction; Dogs -- Fiction; Landscape -- Fiction